AN EXPLICATION OF HOW WEBSITE DESIGN ACTUALLY SHAPES ONLINE CUSTOMER LOYALTY: INCORPORATING SEM AND PERSON-ITEMS MAP ANALYSIS - Wibowo, Hermansyah Andi (Ridwan Institute, 2025)
This article aims to provide a clear picture of how website/application design equates websites with applications, hereinafter referred to as websites, influences the formation of electronic loyalty (eLoy) through electronic trust (eTrust) and electronic satisfaction (eSat), by providing empirical evidence about the relationship between the demographic aspects of respondents and their choice of response to how the website/app is designed by the company. The research employs a laboratory simulation approach by explicating SEM-based results using the PIM feature within the Rasch model. The verified SEM model demonstrates strong goodness of fit, with six indexes indicating satisfactory results. The findings not only enhance theoretical understanding but also lay the groundwork for future research suggestions, demonstrating the potential for serendipitous discoveries in the evolving landscape of online shopping behavior. Future research should focus on refining the methodology for combining SEM and PIM analysis to further enhance the understanding of online consumer loyalty through website design.